Facial emotion memory in schizophrenia: From encoding to maintenance-related EEG. Issue 2 (February 2016) - Brenner, Colleen A.; Rumak, Samuel P.; Burns, Amy M.N.
Highlights: Schizophrenia and control subjects completed a novel facial emotion memory task. Sensory ERPs, sustained theta power and their relationship was measured. Group differences in N170, theta power and their correlations are reported. Abstract: Objective: Persons with schizophrenia exhibit deficits recognizing facial emotions, which may impact social functioning. Whether these deficits reflect aberrant sensory processing, an inability to maintain information in memory, or dysfunctional integration of these two functions remains unclear. Methods: A facial emotion memory paradigm was administered to 38 schizophrenia patients (SZ) and 42 healthy controls (HC). P100, N170 and N250 ERP amplitudes were measured to assess sensory processing. Evoked theta power during the delay interval was quantified to assess memory maintenance. Results: The N170 ERP was larger to negative compared to neutral facial expressions in both groups, while SZ exhibited increased evoked theta power during the delay interval. Increased theta power was associated with worse behavioral performance in response to sad and fearful expressions for HC, but this relationship was only found in response to fearful expressions for SZ. Finally, only HC showed consistent correlations between N170 amplitude and theta power during the delay interval. Conclusions: Integration between measures of sensory processing and memory functioning may be affected in SZ. Significance: These findings may indicate that the oscillatory networks subserving emotion processing and sustained attention are intertwined, and comprise part of the social brain network that is affected in schizophrenia.